The Role of the GREENWOOD Business Park in Increasing the Volume of Trade between China and Russia - Guobai Yang; Elena Kolganova (Communications of International Proceedings, 2021)
Having won an impressive target audience in the home market, many companies do not stop there and move on to the next stage of development: they start preparing for expansion into foreign markets. Going to the international level is a great success for any company, but not everyone succeeds. To move beyond the home market and hold its ground, a company will have to organize itself according to a host of new factors that it hasn't had to deal with within its home country. Therefore, it is important to outline the general picture of the actions required to launch operations in foreign markets. Winning and maintaining positions in foreign markets is much more difficult than simply announcing the globalization of a company and waiting for income from sales abroad. Organization of marketing and sales in any other country requires careful preparation and study of a number of the most important aspects of working in this market. The company needs to understand how much the product or service it produces is in demand on the world market. This may seem self-evident in the very early stages of a business, but the product or service must be viable in the market to which the company plans to export it. Thus, the relevance of the work is reflected in the fact that for any enterprise wishing to enter into international economic relations, first of all, it is necessary to ensure a successful entry into the foreign market, which is its main task. In this regard, it is necessary for the company to competently form a strategy for its activities in the market. One of such businesses on the international market is the construction of business parks, which are a unique mechanism for integrating science, industry and education. They help to solve the socio-economic problems of countries, serve as a means of supporting start-up entrepreneurs, a source for innovative business, and a basis for economic and business education. One of these business parks is GREENWOOD, located in Russia. This article will examine its activities and development prospects in the Russian territory.
Keywords: Business Park; International Economic Relations; Strategy.